Fire-resistant bus duct and production method thereof

By using a specific proper refractory material in the fire -resistant parent line, including liquid epoxy resin, inorganic refractory fillers, silicon tungsten acid modified pyrine -doped magnesium aluminum -like dual -metallic hydroxide and silicon dioxide short -cut carbon fiber The problem of insufficient strength of the existing refractory materials has been solved, and the comprehensive improvement of high -powered performance, excellent refractory performance and good environmental protection properties have been achieved.

CN119371779APending Publication Date: 2025-01-28HANGZHOU MAIXUN ELECTRICAL EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410669735.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When the existing cast-type refractory bus ducts ensure refractory resistance and environmental protection, the strength of the refractory material is low, which affects its performance.

Method used

Adopt the refractory material including liquid epoxy resin, inorganic refractory filler, silicon tungsten acid modified magnesium aluminum -like hydroxide, and silicon dioxide short -cut carbon fiber. Improve the mechanical performance and flame retardant performance of materials.

Benefits of technology

It significantly improves the mechanical performance and refractory performance of the refractory mother line groove, extended the service life, while maintaining good environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004862301030000101
    Figure BDA0004862301030000101
  • Figure BDA0004862301030000111
    Figure BDA0004862301030000111
Patent Text Reader

Abstract

The invention relates to the technical field of fire-resistant bus ducts, in particular to a fire-resistant bus duct and a production method thereof.The fire-resistant bus duct comprises a fire-resistant material and a bus fixed in the fire-resistant material; the refractory material is prepared from the following raw materials in parts by weight: 100 parts of liquid epoxy resin, 38 to 57 parts of inorganic refractory filler, 23 to 32 parts of silicotungstic acid modified yttrium doped magnesium aluminum layered double hydroxide, 5 to 12 parts of silicon dioxide modified short carbon fiber and 34 to 40 parts of curing agent. The fire-resistant bus duct prepared by the invention has excellent mechanical properties and fire resistance, and meanwhile, is high in environmental protection property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fire-resistant bus ducts, and in particular to a fire-resistant bus duct and a production method thereof. Background Art

[0002] Bus duct is used to distribute high power to each component of the distributed system. It has increasingly replaced wires and cables in indoor low-voltage power transmission trunk line projects.

[0003] Among them, cast-type fire-resistant bus duct is a bus duct that directly casts and seals the busbar, which is generally composed of busbar, shell, etc. The busbar is a copper or aluminum busbar made of conductive material, and the shell is a refractory material that is cast and solidified with a mixture of insulating resin and inorganic minerals, and has good insulation and fire resistance. The cast-type fire-resistant bus duct maintains structural integrity for a long time in a high temperature environment, will not melt or deform due to heat, and has excellent fireproof and heat-insulating properties, and can isolate flames and high temperatures. At the same time. The cast-type fire-resistant bus duct also has excellent corrosion resistance, can be widely used and has a long service life.

[0004] Cast-type refractory bus duct is generally composed of multiple refractory cast bus duct units that are assembled and connected. The refractory cast bus duct unit is the main structure of the cast-type refractory bus duct, so it has high requirements for the refractory materials involved, not only requiring them to have excellent fire resistance, but also excellent mechanical properties and environmental protection performance. However, in order to ensure the fire resistance and environmental protection of the refractory materials, a large amount of inorganic minerals and some inorganic flame retardants will be added to the refractory materials. This large amount of addition will reduce the strength of the refractory materials to a certain extent, thereby affecting their performance. Summary of the invention

[0005] The object of the present invention is to provide a fire-resistant bus duct and a production method thereof. The prepared fire-resistant bus duct has excellent mechanical properties and fire resistance and is highly environmentally friendly.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0007] A refractory bus duct comprises a refractory material and a busbar fixed in the refractory material. The refractory material comprises the following raw materials in parts by weight: 100 parts of liquid epoxy resin, 38-57 parts of inorganic refractory filler, 23-32 parts of silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide, 5-12 parts of silica modified short chopped carbon fiber, and 34-40 parts of curing agent.

[0008] Preferably, the preparation method of the silica-modified chopped carbon fiber comprises the following steps: adding chopped carbon fiber and silica sol into water, stirring and dispersing to obtain a mixed solution; placing the mixed solution in a reaction kettle, sealing it, heating it to 80-90°C and maintaining it for 1.5-2h, then centrifuging it, and then drying it to obtain pre-modified chopped carbon fiber; then, in a nitrogen atmosphere, heating the pre-modified chopped carbon fiber to 350-400°C and maintaining it for 2-3h to obtain silica-modified chopped carbon fiber.

[0009] Preferably, the diameter of the chopped carbon fiber is 5-12 μm, and the length is 500-1000 μm; the particle size of silicon dioxide in the silica sol is 10-30 nm, and the concentration of the silica sol is 30-40%.

[0010] Preferably, the mass ratio of water, chopped carbon fibers and silica sol is 100:3-7:10-15.

[0011] Preferably, the preparation method of the silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide comprises the following steps:

[0012] 1) In a nitrogen atmosphere, a metal salt solution containing yttrium nitrate, magnesium nitrate, aluminum nitrate and an alkali solution are simultaneously added dropwise to deionized water, and the mixture is stirred during the addition process, and the temperature is controlled to be 50-55° C. and the pH value is controlled to be between 9-9.5. After the addition is completed, the mixture is heated to 70-75° C. and the reaction is continued for 12-15 hours. The mixture is centrifuged and washed, and dried to obtain a yttrium-doped magnesium-aluminum layered double metal hydroxide;

[0013] 2) H3SiW 12 O 40 Dissolve in deionized water, add NaOH to neutralize to obtain a sodium silicotungstate solution; add yttrium-doped magnesium-aluminum layered double metal hydroxide to deionized water, and stir to obtain a slurry; under a nitrogen atmosphere, drop the sodium silicotungstate solution into the slurry, stir while adding, and after the addition is completed, heat to 60-65°C to react for 12-15h, then filter and wash with deionized water, and vacuum dry to obtain the silicotungstate modified yttrium-doped magnesium-aluminum layered double metal hydroxide.

[0014] Preferably, in step 1), in the metal salt solution, the molar ratio of yttrium nitrate, magnesium nitrate and aluminum nitrate is 0.05-0.08:2.7-3.2:1; the molar concentration of aluminum nitrate is 0.15-0.3 mol / L;

[0015] The alkali solution contains sodium hydroxide and sodium carbonate, the molar ratio of sodium hydroxide to sodium carbonate is 1:0.25-0.5; the molar concentration of the sodium hydroxide is 0.2-0.3 mol / L;

[0016] In step 2), H3SiW12 O 40 Dissolved in deionized water 15-20 times its mass; adding yttrium-doped magnesium-aluminum layered double hydroxide to deionized water 20-30 times its mass; the H3SiW 12 O 40 The mass ratio of yttrium-doped magnesium aluminum layered double hydroxide is 1:3-4.

[0017] Preferably, the inorganic refractory filler is composed of the following raw materials in weight percentage: 60-85% of magnesia-alumina spinel powder and 15-40% of spodumene powder.

[0018] Preferably, the particle size of the magnesia-alumina spinel powder is 100-300 μm, and the particle size of the spodumene powder is 5-10 μm.

[0019] Preferably, the liquid epoxy resin is one or more of epoxy resin E44 and epoxy resin E51; and the curing agent is curing agent D230.

[0020] As a general inventive concept, the present invention provides a method for producing a fire-resistant bus duct, comprising the following steps:

[0021] (1) placing a busbar in a mold and fixing it at a corresponding position; then mixing the raw inorganic refractory filler, silicotungstic acid-modified yttrium-doped magnesium-aluminum layered double metal hydroxide, and silica-modified chopped carbon fiber in the refractory material evenly, adding them to liquid epoxy resin and mixing them evenly, and then adding a curing agent and mixing them evenly to obtain a refractory castable; introducing the refractory castable into a mold to obtain a mold after casting;

[0022] (2) The mold after pouring is first heated to 100-105°C at a heating rate of 5-9°C / min, kept warm for 1-1.5h, then heated to 130-135°C at a heating rate of 3-5°C / min, kept warm for 1.5-2h, then heated to 145-150°C at a heating rate of 1-2°C / min, kept warm for 1.5-2h, and then cooled to room temperature.

[0023] The beneficial effects of the present invention are:

[0024] 1. The fiber reinforcement added to the refractory material of the present invention is silica-modified chopped carbon fiber. Since the surface of the chopped carbon fiber is loaded with nano-silicon dioxide, on the one hand, the compatibility between the chopped carbon fiber and the resin can be improved. On the other hand, the nano-silicon dioxide of the chopped carbon fiber can be embedded in the resin as an anchor point, thereby increasing the bonding force between the resin and the anchor point. At the same time, the anchor point will also be embedded with the inorganic refractory filler in the refractory material, so that the silica-modified chopped carbon fiber and the matrix are not easy to peel off under the action of external force. On the basis of the above, combined with the reinforcement performance of the chopped carbon fiber itself, the mechanical properties of the refractory material can be effectively improved, and the service life of the refractory bus duct can be extended.

[0025] 2. The flame retardant in the present invention is mainly yttrium-doped magnesium-aluminum layered double metal hydroxide modified by silicotungstic acid. Yttrium-doping the magnesium-aluminum layered double metal hydroxide can improve its structural stability under high temperature environment, promote the release of water and carbon dioxide during combustion, accelerate the formation of dense carbon layer, and enhance flame retardancy. Yttrium-doped magnesium-aluminum layered double metal hydroxide is modified by silicotungstic acid intercalation, and its interlayer anions can be replaced with silicotungstic acid anions with higher flame retardancy, thereby effectively increasing the flame retardancy. Modifying the magnesium-aluminum layered double metal hydroxide in the above manner can significantly increase its flame retardancy. Therefore, even if a small amount of yttrium-doped magnesium-aluminum layered double metal hydroxide modified by silicotungstic acid is added, it can achieve a good flame retardant and fire resistant effect when combined with the inorganic refractory filler of the present invention, and keep the refractory material at a high mechanical property. When the above-mentioned yttrium-doped magnesium-aluminum layered double metal hydroxide modified by silicotungstic acid is used as a flame retardant, its decomposition products are mainly water and carbon dioxide, which has a high environmental performance. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Preparation Example 1:

[0028] A method for preparing silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide comprises the following steps:

[0029] 1) In a nitrogen atmosphere, a metal salt solution and an alkali solution are simultaneously added dropwise to deionized water, and the mixture is stirred during the addition process. The temperature is controlled at 55° C. and the pH value is controlled at 9-9.5. After the addition is completed, the mixture is heated to 75° C. and the reaction is continued for 13 hours. The mixture is washed by centrifugation and dried to obtain a yttrium-doped magnesium-aluminum layered double metal hydroxide.

[0030] The metal salt solution contains yttrium nitrate, magnesium nitrate and aluminum nitrate, and the molar ratio of yttrium nitrate, magnesium nitrate and aluminum nitrate is 0.06:3:1; the molar concentration of aluminum nitrate is 0.3 mol / L. The alkali solution contains sodium hydroxide and sodium carbonate, and the molar ratio of sodium hydroxide and sodium carbonate is 1:0.5; the molar concentration of sodium hydroxide is 0.2 mol / L.

[0031] 2) H3SiW 12 O 40 Dissolve in deionized water 20 times its mass, add NaOH to neutralize to obtain sodium silicotungstate solution; add yttrium-doped magnesium-aluminum layered double metal hydroxide to deionized water 20 times its mass, stir to obtain slurry, H3SiW 12 O 40 The mass ratio of yttrium-doped magnesium aluminum layered double hydroxide is 1:4; under a nitrogen atmosphere, sodium silicotungstate solution is added dropwise to the slurry while stirring. After the addition is completed, the temperature is raised to 60°C and the reaction is carried out for 13 hours. Then it is filtered and washed with deionized water, and vacuum dried to obtain silicotungstic acid modified yttrium-doped magnesium aluminum layered double hydroxide.

[0032] Preparation Example 2:

[0033] A method for preparing silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide comprises the following steps:

[0034] 1) In a nitrogen atmosphere, a metal salt solution and an alkali solution are simultaneously added dropwise to deionized water, and the mixture is stirred during the addition process. The temperature is controlled at 50° C. and the pH value is controlled at 9-9.5. After the addition is completed, the mixture is heated to 70° C. and the reaction is continued for 12 hours. The mixture is centrifuged and washed, and dried to obtain a yttrium-doped magnesium-aluminum layered double hydroxide.

[0035] The metal salt solution contains yttrium nitrate, magnesium nitrate and aluminum nitrate, and the molar ratio of yttrium nitrate, magnesium nitrate and aluminum nitrate is 0.05:2.7:1; the molar concentration of aluminum nitrate is 0.15 mol / L. The alkali solution contains sodium hydroxide and sodium carbonate, and the molar ratio of sodium hydroxide to sodium carbonate is 1:0.35; the molar concentration of sodium hydroxide is 0.3 mol / L.

[0036] 2) H3SiW 12 O 40 Dissolve in deionized water 15 times its mass, add NaOH to neutralize to obtain sodium silicotungstate solution; add yttrium-doped magnesium-aluminum layered double metal hydroxide to deionized water 30 times its mass, stir to obtain slurry, H3SiW 12 O 40The mass ratio of yttrium-doped magnesium aluminum layered double hydroxide is 1:3; under a nitrogen atmosphere, sodium silicotungstate solution is added dropwise to the slurry while stirring. After the addition is completed, the temperature is raised to 65°C and the reaction is carried out for 15 hours. Then it is filtered and washed with deionized water, and vacuum dried to obtain silicotungstic acid modified yttrium-doped magnesium aluminum layered double hydroxide.

[0037] Preparation Example 3:

[0038] A method for preparing silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide comprises the following steps:

[0039] 1) In a nitrogen atmosphere, a metal salt solution and an alkali solution are simultaneously added dropwise to deionized water, and the mixture is stirred during the addition process. The temperature is controlled at 52° C. and the pH value is controlled at 9-9.5. After the addition is completed, the mixture is heated to 75° C. and the reaction is continued for 15 hours. The mixture is washed by centrifugation and dried to obtain a yttrium-doped magnesium-aluminum layered double hydroxide.

[0040] The metal salt solution contains yttrium nitrate, magnesium nitrate and aluminum nitrate, and the molar ratio of yttrium nitrate, magnesium nitrate and aluminum nitrate is 0.08:3.2:1; the molar concentration of aluminum nitrate is 0.3 mol / L. The alkali solution contains sodium hydroxide and sodium carbonate, and the molar ratio of sodium hydroxide to sodium carbonate is 1:0.25; the molar concentration of sodium hydroxide is 0.2 mol / L.

[0041] 2) H3SiW 12 O 40 Dissolve it in deionized water 18 times its mass, add NaOH to neutralize it to obtain sodium silicotungstate solution; add yttrium-doped magnesium-aluminum layered double metal hydroxide to deionized water 25 times its mass, stir to obtain slurry, H3SiW 12 O 40 The mass ratio of yttrium-doped magnesium aluminum layered double hydroxide is 1:3.5; under a nitrogen atmosphere, sodium silicotungstate solution is added dropwise to the slurry while stirring. After the addition is completed, the temperature is raised to 62°C and the reaction is carried out for 12 hours. Then it is filtered and washed with deionized water, and vacuum dried to obtain silicotungstic acid modified yttrium-doped magnesium aluminum layered double hydroxide.

[0042] Preparation Example 4:

[0043] A method for preparing silica-modified chopped carbon fibers comprises the following steps: adding 5 parts of chopped carbon fibers and 15 parts of silica sol into 100 parts of water, stirring and dispersing to obtain a mixed solution; placing the mixed solution in a reaction kettle, sealing it, heating it to 90°C and keeping it for 1.5 hours, then centrifuging it, and drying it to obtain pre-modified chopped carbon fibers; then, in a nitrogen atmosphere, heating the pre-modified chopped carbon fibers to 380°C and keeping it for 3 hours to obtain silica-modified chopped carbon fibers.

[0044] The diameter of the chopped carbon fiber is 10 μm and the length is 5800 μm; the particle size of silicon dioxide in the silica sol is 10-30 nm, and the concentration of the silica sol is 35%.

[0045] Preparation Example 5:

[0046] A method for preparing silica-modified chopped carbon fibers comprises the following steps: adding 3 parts of chopped carbon fibers and 12 parts of silica sol into 100 parts of water, stirring and dispersing to obtain a mixed solution; placing the mixed solution in a reaction kettle, sealing it, heating it to 80°C and keeping it for 2 hours, then centrifuging it, and drying it to obtain pre-modified chopped carbon fibers; then, in a nitrogen atmosphere, heating the pre-modified chopped carbon fibers to 400°C and keeping it for 2 hours to obtain silica-modified chopped carbon fibers.

[0047] The diameter of the chopped carbon fiber is 5 μm and the length is 500 μm; the particle size of silicon dioxide in the silica sol is 10-30 nm, and the concentration of the silica sol is 30%.

[0048] Preparation Example 6:

[0049] A method for preparing silica-modified chopped carbon fibers comprises the following steps: adding 7 parts of chopped carbon fibers and 10 parts of silica sol into 100 parts of water, stirring and dispersing to obtain a mixed solution; placing the mixed solution in a reaction kettle, sealing it, heating it to 85°C and keeping it for 2 hours, then centrifuging it, and drying it to obtain pre-modified chopped carbon fibers; then, in a nitrogen atmosphere, heating the pre-modified chopped carbon fibers to 350°C and keeping it for 2.5 hours to obtain silica-modified chopped carbon fibers.

[0050] The diameter of the chopped carbon fiber is 12 μm and the length is 1000 μm; the particle size of silicon dioxide in the silica sol is 10-30 nm, and the concentration of the silica sol is 40%.

[0051] Embodiment 1:

[0052] A refractory bus duct comprises a refractory material and a busbar fixed in the refractory material, wherein the refractory material comprises the following raw materials in parts by weight: 100 parts of epoxy resin E51, 50 parts of inorganic refractory filler, 23 parts of silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide, 7 parts of silica modified short chopped carbon fiber, and 38 parts of curing agent D230.

[0053] The inorganic refractory filler is composed of the following raw materials in weight percentage: 75% of magnesium aluminum spinel powder and 25% of spodumene powder. The particle size of the magnesium aluminum spinel powder is 100-300 μm, and the particle size of the spodumene powder is 5-10 μm.

[0054] The silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide is prepared by the method in Preparation Example 2. The silicon dioxide modified short chopped carbon fiber is prepared by the method in Preparation Example 6.

[0055] The production method of the above-mentioned fire-resistant bus duct comprises the following steps:

[0056] (1) placing a busbar in a mold and fixing it at a corresponding position; then mixing the raw inorganic refractory filler, silicotungstic acid-modified yttrium-doped magnesium-aluminum layered double metal hydroxide, and silica-modified chopped carbon fiber in the refractory material evenly, adding them to the liquid epoxy resin and mixing them evenly, and then adding a curing agent and mixing them evenly to obtain a refractory castable; introducing the refractory castable into a mold to obtain a mold after casting;

[0057] (2) The mold after pouring is first heated to 105°C at a heating rate of 8°C / min, kept warm for 1 hour, then heated to 130°C at a heating rate of 5°C / min, kept warm for 2 hours, then heated to 150°C at a heating rate of 2°C / min, kept warm for 1.5 hours, and then cooled to room temperature.

[0058] Embodiment 2:

[0059] A refractory bus duct comprises a refractory material and a busbar fixed in the refractory material, wherein the refractory material comprises the following raw materials in parts by weight: 100 parts of epoxy resin E51, 38 parts of inorganic refractory filler, 32 parts of silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide, 5 parts of silica modified short chopped carbon fiber, and 40 parts of curing agent D230.

[0060] The inorganic refractory filler is composed of the following raw materials in weight percentage: 85% of magnesium aluminum spinel powder and 15% of spodumene powder. The particle size of the magnesium aluminum spinel powder is 100-300 μm, and the particle size of the spodumene powder is 5-10 μm.

[0061] The silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide is prepared by the method in Preparation Example 1. The silicon dioxide modified short chopped carbon fiber is prepared by the method in Preparation Example 4.

[0062] The production method of the above-mentioned fire-resistant bus duct comprises the following steps:

[0063] (1) placing a busbar in a mold and fixing it at a corresponding position; then mixing the raw inorganic refractory filler, silicotungstic acid-modified yttrium-doped magnesium-aluminum layered double metal hydroxide, and silica-modified chopped carbon fiber in the refractory material evenly, adding them to the liquid epoxy resin and mixing them evenly, and then adding a curing agent and mixing them evenly to obtain a refractory castable; introducing the refractory castable into a mold to obtain a mold after casting;

[0064] (2) The mold after pouring is first heated to 100°C at a heating rate of 5°C / min, kept warm for 1.5 hours, then heated to 135°C at a heating rate of 3°C / min, kept warm for 1.5 hours, then heated to 145°C at a heating rate of 1°C / min, kept warm for 2 hours, and then cooled to room temperature.

[0065] Embodiment 3:

[0066] A refractory bus duct comprises a refractory material and a busbar fixed in the refractory material, wherein the refractory material comprises the following raw materials in parts by weight: 100 parts of epoxy resin E51, 57 parts of inorganic refractory filler, 30 parts of silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide, 12 parts of silica modified short chopped carbon fiber, and 34 parts of curing agent D230.

[0067] The inorganic refractory filler is composed of the following raw materials in weight percentage: 60% of magnesium aluminum spinel powder and 40% of spodumene powder. The particle size of the magnesium aluminum spinel powder is 100-300 μm, and the particle size of the spodumene powder is 5-10 μm.

[0068] The silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide is prepared by the method in Preparation Example 3. The silicon dioxide modified short chopped carbon fiber is prepared by the method in Preparation Example 5.

[0069] The production method of the above-mentioned fire-resistant bus duct comprises the following steps:

[0070] (1) placing a busbar in a mold and fixing it at a corresponding position; then mixing the raw inorganic refractory filler, silicotungstic acid-modified yttrium-doped magnesium-aluminum layered double metal hydroxide, and silica-modified chopped carbon fiber in the refractory material evenly, adding them to the liquid epoxy resin and mixing them evenly, and then adding a curing agent and mixing them evenly to obtain a refractory castable; introducing the refractory castable into a mold to obtain a mold after casting;

[0071] (2) The mold after pouring is first heated to 105°C at a heating rate of 9°C / min, kept warm for 1 hour, then heated to 135°C at a heating rate of 4°C / min, kept warm for 1.5 hours, then heated to 145°C at a heating rate of 1°C / min, kept warm for 1.5 hours, and then cooled to room temperature.

[0072] Embodiment 4:

[0073] A refractory bus duct comprises a refractory material and a busbar fixed in the refractory material, wherein the refractory material comprises the following raw materials in parts by weight: 100 parts of epoxy resin E51, 45 parts of inorganic refractory filler, 28 parts of silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide, 10 parts of silica modified short chopped carbon fiber, and 35 parts of curing agent D230.

[0074] The inorganic refractory filler is composed of the following raw materials in weight percentage: 70% of magnesium aluminum spinel powder and 30% of spodumene powder. The particle size of the magnesium aluminum spinel powder is 100-300 μm, and the particle size of the spodumene powder is 5-10 μm.

[0075] The silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide is prepared by the method in Preparation Example 2. The silicon dioxide modified short chopped carbon fiber is prepared by the method in Preparation Example 5.

[0076] The production method of the above-mentioned fire-resistant bus duct is the same as that of Example 1.

[0077] Embodiment 5:

[0078] A refractory bus duct comprises a refractory material and a busbar fixed in the refractory material, wherein the refractory material comprises the following raw materials in parts by weight: 100 parts of epoxy resin E51, 52 parts of inorganic refractory filler, 25 parts of silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide, 8 parts of silica modified short chopped carbon fiber, and 34 parts of curing agent D230.

[0079] The inorganic refractory filler is composed of the following raw materials in weight percentage: 80% of magnesium aluminum spinel powder and 20% of spodumene powder. The particle size of the magnesium aluminum spinel powder is 100-300 μm, and the particle size of the spodumene powder is 5-10 μm.

[0080] The silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide was prepared by the method in Preparation Example 3. The silicon dioxide modified short chopped carbon fiber was prepared by the method in Preparation Example 6.

[0081] The production method of the above-mentioned fire-resistant bus duct is the same as that of Example 2.

[0082] Comparative Example 1:

[0083] The difference from Example 5 is that the silica-modified chopped carbon fibers are replaced by chopped carbon fibers. The chopped carbon fibers have a diameter of 12 μm and a length of 1000 μm.

[0084] Comparative Example 2:

[0085] Different from Example 5, the silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide is replaced by magnesium aluminum layered double metal hydroxide, and the preparation method of magnesium aluminum layered double metal hydroxide comprises the following steps:

[0086] Under a nitrogen atmosphere, metal salt solution and alkali solution are simultaneously added to deionized water with stirring during the addition process, and the temperature is controlled at 52°C and the pH is between 9-9.5. After the addition is completed, the temperature is raised to 75°C and the reaction is continued for 15 hours. The mixture is centrifuged and washed, and dried to obtain a magnesium-aluminum layered double metal hydroxide.

[0087] The metal salt solution contains magnesium nitrate and aluminum nitrate, the molar ratio of magnesium nitrate to aluminum nitrate is 3.2:1, and the molar concentration of aluminum nitrate is 0.3 mol / L. The alkali solution contains sodium hydroxide and sodium carbonate, the molar ratio of sodium hydroxide to sodium carbonate is 1:0.25, and the molar concentration of sodium hydroxide is 0.2 mol / L.

[0088] The fire resistance test was conducted in accordance with the test standard of GA / T537-2005 "Test Method Standard for Flame Retardant, Fireproof and Fire Resistance of Bus Trunk System (Bus Trunk)", and the test piece was kept intact at 1100℃ for the fire resistance time of the line. The tensile strength and bending strength were conducted in accordance with the test standard of GB / T2567-2008 "Test Method for Performance of Resin Casting". The specific test results are shown in Table 1.

[0089] Table 1:

[0090]

[0091]

[0092] As shown in Table 1, the fire-resistant bus ducts in Examples 1-5 of the present invention all have excellent fire resistance and mechanical properties, with a fire resistance time of up to 210 min, a tensile strength of more than 72 MPa, and a bending strength of more than 165 MPa. By comparing Comparative Example 1 with Example 5, it can be seen that the modification of chopped carbon fibers with silica can significantly enhance the mechanical properties of the refractory material and improve the fire resistance. By comparing Comparative Example 2 with Example 5, it can be seen that the yttrium doping and silicotungstic acid modification of magnesium-aluminum layered double hydroxides can significantly improve the fire resistance of the fire-resistant bus duct.

[0093] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A refractory bus duct, comprising a refractory material and a busbar fixed in the refractory material, characterized in that: The refractory material comprises the following raw materials in parts by weight: 100 parts of liquid epoxy resin, 38-57 parts of inorganic refractory filler, 23-32 parts of silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide, 5-12 parts of silicon dioxide modified short chopped carbon fiber, and 34-40 parts of curing agent.

2. The fire-resistant bus duct according to claim 1, characterized in that: The preparation method of the silica-modified chopped carbon fiber comprises the following steps: adding chopped carbon fiber and silica sol into water, stirring and dispersing to obtain a mixed solution; placing the mixed solution in a reaction kettle, sealing it, heating it to 80-90° C. and maintaining it for 1.5-2 hours, then centrifuging it, and drying it to obtain pre-modified chopped carbon fiber; and then heating the pre-modified chopped carbon fiber to 350-400° C. and maintaining it for 2-3 hours under a nitrogen atmosphere to obtain the silica-modified chopped carbon fiber.

3. The fire-resistant bus duct according to claim 2, characterized in that: The diameter of the chopped carbon fiber is 5-12 μm, and the length is 500-1000 μm; the particle size of silicon dioxide in the silica sol is 10-30 nm, and the concentration of the silica sol is 30-40%.

4. The fire-resistant bus duct according to claim 2, characterized in that: The mass ratio of the water, the chopped carbon fibers and the silica sol is 100:3-7:10-15.

5. The fire-resistant bus duct according to claim 1, characterized in that: The preparation method of the silicotungstic acid modified yttrium doped magnesium aluminum layered double metal hydroxide comprises the following steps: 1) In a nitrogen atmosphere, a metal salt solution containing yttrium nitrate, magnesium nitrate, aluminum nitrate and an alkali solution are simultaneously added dropwise to deionized water, and the mixture is stirred during the addition process, and the temperature is controlled to be 50-55° C. and the pH value is controlled to be between 9-9.

5. After the addition is completed, the mixture is heated to 70-75° C. and the reaction is continued for 12-15 hours. The mixture is centrifuged and washed, and dried to obtain a yttrium-doped magnesium-aluminum layered double metal hydroxide; 2) H3SiW 12 O 40 Dissolve in deionized water, add NaOH to neutralize to obtain a sodium silicotungstate solution; add yttrium-doped magnesium-aluminum layered double metal hydroxide to deionized water, and stir to obtain a slurry; under a nitrogen atmosphere, drop the sodium silicotungstate solution into the slurry, stir while adding, and after the addition is completed, heat to 60-65°C to react for 12-15h, then filter and wash with deionized water, and vacuum dry to obtain the silicotungstate modified yttrium-doped magnesium-aluminum layered double metal hydroxide.

6. The fire-resistant bus duct according to claim 5, characterized in that: In step 1), in the metal salt solution, the molar ratio of yttrium nitrate, magnesium nitrate and aluminum nitrate is 0.05-0.08:2.7-3.2:1; the molar concentration of aluminum nitrate is 0.15-0.3 mol / L; The alkali solution contains sodium hydroxide and sodium carbonate, the molar ratio of sodium hydroxide to sodium carbonate is 1:0.25-0.5; the molar concentration of the sodium hydroxide is 0.2-0.3 mol / L; In step 2), H3SiW 12 O 40 Dissolved in deionized water 15-20 times its mass; adding yttrium-doped magnesium-aluminum layered double hydroxide to deionized water 20-30 times its mass; the H3SiW 12 O 40 The mass ratio of yttrium-doped magnesium aluminum layered double hydroxide is 1:3-4.

7. The fire-resistant bus duct according to claim 1, characterized in that: The inorganic refractory filler is composed of the following raw materials in weight percentage: 60-85% of magnesia-alumina spinel powder and 15-40% of spodumene powder.

8. The fire-resistant bus duct according to claim 7, characterized in that: The particle size of the magnesium aluminum spinel powder is 100-300 μm, and the particle size of the spodumene powder is 5-10 μm.

9. The fire-resistant bus duct according to claim 1, characterized in that: The liquid epoxy resin is one or more of epoxy resin E44 and epoxy resin E51; the curing agent is curing agent D230.

10. A method for producing a fire-resistant bus duct according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) placing a busbar in a mold and fixing it at a corresponding position; then mixing the raw inorganic refractory filler, silicotungstic acid-modified yttrium-doped magnesium-aluminum layered double metal hydroxide, and silica-modified chopped carbon fiber in the refractory material evenly, adding them to liquid epoxy resin and mixing them evenly, and then adding a curing agent and mixing them evenly to obtain a refractory castable; introducing the refractory castable into a mold to obtain a mold after casting; (2) The mold after pouring is first heated to 100-105°C at a heating rate of 5-9°C / min, kept warm for 1-1.5h, then heated to 130-135°C at a heating rate of 3-5°C / min, kept warm for 1.5-2h, then heated to 145-150°C at a heating rate of 1-2°C / min, kept warm for 1.5-2h, and then cooled to room temperature.